Hubungan Tingkat Pengetahuan Dengan Sikap Masyarakat Dalam Memberikan Pertolongan Pada Korban Henti Jantung - Deswita, Reny; Siti Khoirun Nisa; Popy Irawati (Journal of Pubnursing Sciences, 2024)
Background: the death rate due to cardiac arrest is still very high, namely around 475,000 deaths. Cardiac arrest conditions must be given immediate assistance because it can disrupt blood circulation throughout the body. The general public has a very important role in providing first aid to victims of cardiac arrest that occur outside the hospital. Objective: to determine the relationship between the level of knowledge and community attitudes in providing aid to cardiac arrest patients in RW 04, Batu Ceper Village. Method: using a cross sectional research design, a sample of 93 respondents, using a purposive sampling technique, data was obtained by giving questionnaires to respondents which were then processed using the Spearman Rank analysis test. Results: 45 people (48.4%) had a poor level of knowledge with 56 people (60.2%) having a bad attitude from the community. There is a significant relationship between the level of knowledge and people's attitudes with a p value (0.000) < α (0.05). Conclusion: the higher the level of public knowledge, the better their attitude in providing aid to cardiac arrest patients.